The Human 2-Cys Peroxiredoxins form Widespread, Cysteine-Dependent- and Isoform-Specific Protein-Protein Interactions - Loes van Dam; Marc Pagès-Gallego; Paulien E. Polderman; Robert M. van Es; Boudewijn M. T. Burgering; Harmjan R. Vos; Tobias B. Dansen (MDPI AG, 2021)
Redox signaling is controlled by the reversible oxidation of cysteine thiols, a post-translational modification triggered by H2O2 acting as a second messenger. However, H2O2 actually reacts poorly with most cysteine thiols and it is not clear how H2O2 discriminates between cysteines to trigger appropriate signaling cascades in the presence of dedicated H2O2 scavengers like peroxiredoxins (PRDXs). It was recently suggested that peroxiredoxins act as peroxidases and facilitate H2O2-dependent oxidation of redox-regulated proteins via disulfide exchange reactions. It is unknown how the peroxiredoxin-based relay model achieves the selective substrate targeting required for adequate cellular signaling. Using a systematic mass-spectrometry-based approach to identify cysteine-dependent interactors of the five human 2-Cys peroxiredoxins, we show that all five human 2-Cys peroxiredoxins can form disulfide-dependent heterodimers with a large set of proteins. Each isoform displays a preference for a subset of disulfide-dependent binding partners, and we explore isoform-specific properties that might underlie this preference. We provide evidence that peroxiredoxin-based redox relays can proceed via two distinct molecular mechanisms. Altogether, our results support the theory that peroxiredoxins could play a role in providing not only reactivity but also selectivity in the transduction of peroxide signals to generate complex cellular signaling responses.